Molecular biological elucidation of late tropane alkaloid biosynthesis - Kohnen-Johannsen, Kathrin Laura (Technische Universität Dortmund, 2019)
Tropane alkaloids (TA) are important and valuable secondary plant metabolites which occur in the families of Solanaceae, Erythroxylaceae, as well as Convolvulaceae, Moraceae, and Brassicaceae. These plant families produce the TAs hyoscyamine and scopolamine, cocaine, or calystegines, respectively. Due to the medicinal and pharmacological properties of hyoscyamine, scopolamine and cocaine, TA containing plants have been used for thousands of years. Even today, many drugs are derived from TAs and are used in the treatment of various diseases. Of the TAs, scopolamine is the most in demand due to its pharmacological effects and legal status. The market supply of scopolamine is still met by conventional field cultivation of Duboisia hybrids. Climate change is resulting in less-stable growth conditions for traditional farming, which limits the reliability of agricultural yields and has warranted investigation of alternative TA production processes. One proposed approach is to transfer biosynthesis into biotechnological host which would enable TA production in containable and scalable fermentative infrastructure using low-cost compounds like tropine and phenyllactic acid. All TA production approaches require profound knowledge of the biochemical pathways. To date, these pathways have not been fully elucidated, which limits their greater biotechnological application. This thesis seeks to increase the fundamental understanding of the molecular processes of the late stages of TA biosynthesis. This thesis deals with the TA biosynthesis in Duboisia plants which is highly specialized and specifically localized. The spatial distribution of TA in planta, the expression of genes involved in the biosynthesis and the TA pattern during plant development are investigated and described. Moreover, it presents investigations towards identification of the littorine synthase, a currently unknown key enzyme in TA biosynthesis. The results of this research add to our understanding of TA biosynthesis and provides important insights for the future development of alternative bio-production processes.
Keywords: Tropane alkaloid biosynthesis; Duboisia myoporoides; 660; Alkaloide